HUBUNGAN KOMPETENSI SOSIAL DENGAN PERILAKU CYBERBULLYING - Lestari, Desi Triani; Malay, M. Nursalim; Fitriani, Annisa (Al Huwiyah: Journal of Woman and Children Studies, 2021)
AbstractCyberbullying behavior is behavior that threatens or oppresses someone who will have a bad impact on the victim through their actions through social media. Social competence is thought to be a factor that influences the occurrence of cyberbullying behavior. The study aims to analyze the relationship between social competence and cyberbullying behavior. The population in this study were students of the Muamalah Study Program at the State Islamic University of Raden Intan Lampung batch 2018 totaling 290 students. Researchers used quantitative research methods with purposive sampling and screening techniques first so that the sample in this study was 73 students. Data collection techniques in this study used a psychological scale including the cyberbullying behavior scale, and social competence. The cyberbullying behavior scale is 38 items (α = 0.963), on social competence there are 31 items (α = 0.901). The analysis technique used is a multiple regression analysis technique assisted by the SPSS 21.0 for windows program. The data analyzed showed the following results: 1. Rx1.2.3-y = 0.911 F = 171.458 with a significance of p = 0.000 (p < 0.01). The social competence and parental autonomy support provided an effective contribution of 83% to the dependent variable and 17% generated by other variables outside the study. 2. rx1-y = -0.803 and p = 0.000 (p < 0.01) indicates that there is a significant negative relationship between social competence and cyberbullying behavior in adolescents. 3. rX2-y = -0.833. Keywords: Cyberbullying Behavior, Social Competence, Media